PENYERAPAN ANGGARAN DI PROVINSI ACEH - Fatmayanti, Fatmayanti; sukiyan, Sukiyan; Hadi, Fajri; Hidayat, Muhammad Rahmat; Rusdi, Rusdi (Universitas Sarjanawiyata Tamansiswa, 2023)
Budget absorption is one of the important indicators in evaluating the financial performance of local governments. This study aims to identify the factors influencing budget absorption in Aceh Province by investigating the impact of the previous year's budget balance and local revenue on budget absorption in Aceh Province. The data used is secondary data collected from the financial and budget reports of Aceh Province for the period 2016-2022. The analytical method used is multiple linear regression using SEM PLS software. The results of the study indicate that the independent variables, previous year's budget balance and local revenue, have different impacts on budget absorption in Aceh Province. The implication of this study is the importance of effective and efficient budget management at the local level to ensure optimal budget absorption.